The Influence of Neuromarketing and Emotional Marketing on the Purchase Intention of the Cirebon Community in the Fashion Industry - Gaung Al Faris; Khusnul Khotimah Khotimah; Siska Ernawati Fatimah (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine how Cirebon people’s purchasing intentions in the fashion industry are affected by neuromarketing and emotional marketing. Purchase intentions arise in response to marketing strategies designed by businesses, especially in the context of online shopping. Neuromarketing and emotional marketing strategies are applied to attract attention and build emotional attachments with consumers, who have evolving digital consumption habits. This study used a quantitative approach, namely residents of Cirebon City aged 14 to 54 years. Sampling using the Slovin formula and obtained 400 respondents. Data analysis with (PLS-SEM) approach. The study shows that emotional marketing has more influence on the purchase intention of Cirebon people in the fashion industry. This is because emotional marketing is able to build strong emotional relationships, create attachment to the brand, and present a more personalized and relatable experience for consumers. Meanwhile, neuromarketing also contributes to increasing purchase intention through psychology and neuro-science-based approaches that influence consumers’ decision-making processes. These findings contribute to businesses in the fashion industry in determining a more effective marketing strategy for the people of Cirebon. Emotional marketing and neuromarketing-based strategies can be used to enhance consumer experience, strengthen brand loyalty, and drive purchasing decisions.